Steroid for epidural injection in spinal stenosis: a systematic review and meta-analysis - Liu K; Liu PC; Liu R; Wu X; Cai M (Dove Medical Press, 2015)
Kuan Liu,* Pengcheng Liu,* Run Liu, Xing Wu, Ming Cai Department of Orthopaedics, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China *These authors contributed equally to this work Purpose: To investigate the effectiveness and safety of epidural steroid injections in patients with lumbar spinal stenosis (LSS). Methods: We performed a search on the CENTRAL, Pubmed, Embase and Cochrane databases up to September 2014. We recovered 17 original articles, of which only 10 were in full compliance with the randomized controlled trial (RCT) criteria. These articles were reviewed in an independent and blinded way by two reviewers who were previously trained to extract data and score their quality by the criteria of the Cochrane Handbook (5.1.0). Results: We accepted ten studies with 1,010 participants. There is minimal evidence that shows that epidural steroid injections are better than lidocaine alone, regardless of the mode of epidural injection. There is a fair short-term and long-term benefit for treating spinal stenosis with local anesthetic and steroids. Conclusions: This meta-analysis suggests that epidural steroid injections provide limited improvement in short-term and long-term benefits in LSS patients. Keywords: lumbar spinal stenosis, epidural injection, steroid, local anesthetic, chronic pain